Perceived relevance mediates the relationship between professional identity and attitudes towards interprofessional education in first-year university students - Roberts, L.; Davis, M.; Crabb, Hannah; Broughton, M. (Informa Healthcare, 2017)
© 2017 Taylor & Francis The strength of health science students’ identification with their chosen profession is associated with their attitudes towards interprofessional education (IPE). However, little is known about the factors that might mediate this relationship. In this article, we examine the relationships between professional identification, communication and teamwork skills, perceived relevance of IPE, and positive and negative attitudes towards IPE. A sample of 444 first-year university students from 25 health science professions enrolled in a first-year interprofessional program participated in this research by completing a questionnaire. Data were analysed using path analysis. Positive IPE attitudes were more strongly endorsed than negative IPE attitudes. Perceived relevance of IPE to future careers was the strongest predictor of both positive and negative attitudes to IPE, and fully mediated the effect of professional identity. Self-reported communication and teamwork skills were a significant negative predictor of negative attitudes to IPE only, and the effect was not mediated by perceived relevance. These findings indicate that IPE may be particularly challenging for students who do not have confidence in their abilities to communicate and work effectively in teams. Building these skills through alternative communication technologies may decrease negative attitudes. In order to maintain or increase positive attitudes towards IPE in introductory programs that span professions, the curriculum needs to be designed to demonstrate relevance to the future careers of participating students.